Diagnosis of the Mycobacterium avium subspecies paratuberculosis in tissues of slaughtered buffaloes using fluorescent antibody test - Jatav, Gaya Prasad; Singh, Shoor Vir; Chaubey, Kundan Kumar; Gupta, Saurabh; Jayraw, Anantrao Kashiram; Agrawal, Vivek; Shakya, Mukesh; Choudhary, Rashmi; Jamra, Nirmala (Buffalo Bulletin, 2024)
Paratuberculosis (pTB) caused by Mycobacterium avium subsp. paratuberculosis (MAP), infects domestic livestock leading to chronic diarrhoea (persistent, intermittent or no diarrhoea) and loss in body condition and weights. It is a major disease that adversely affects health and productivity resulting in colossal monetary losses to the livestock industry throughout the world. Association of MAP with inflammatory bowel disease / Crohn’s disease (CD) in humans, established its zoonotic potential and public health significance. Tissues (corrugated mucosal folds) of 20 buffaloes (both the sexes, aged 1 to 10 years) from Malwa division of Madhya Pradesh were anlyzed by fluorescent antibody test (FAT). Out of 20 tissue smears screened, 11 (55.0%) were positive for MAP by FAT.